A method for testing the alkali resistance of vinylidene fluoride polymers

The degradation amount is calculated by contacting vinylidene fluoride polymer with alkali, and the fluorine ion concentration is detected by ion meter, which solves the accuracy and universality of alkali resistance evaluation in the prior art, and achieves fast, simple and accurate alkali resistance Sex test, suitable for vinylidene fluoride polymers in different types and applications.

CN114076779BActive Publication Date: 2025-01-07ZHEJIANG LANTIAN ENVIRONMENTAL PROTECTION HI TECH CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202010819146.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-08-14
Publication Date
2025-01-07
Estimated Expiration
2040-08-14

AI Technical Summary

Technical Problem

The prior art cannot accurately, quickly and easily evaluate the alkali resistance of vinylidene fluoride polymers, and the testing method is poor in universality and cannot be quantitatively evaluated. It is affected by other factors and has a long cycle, so it is only suitable for specific applications.

Method used

The vinylidene fluoride polymer is contacted with alkali, and its degradation amount is calculated. The alkali resistance is quantitatively evaluated by the amount of fluoride ions. The fluoride ion concentration is detected by an ion meter, and diluted to an appropriate pH value after neutralization to ensure the accuracy of the detection results. and universality.

Benefits of technology

It has achieved accurate evaluation of alkali resistance of vinylidene fluoride polymers, which is fast and simple, and is suitable for alkali resistance tests in different types and applications. It eliminates the influence of factors such as molecular weight and crystallization, and has accurate detection results and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114076779B_ABST
    Figure CN114076779B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for testing the alkali resistance of a vinylidene fluoride polymer. The method quantitatively evaluates the alkali resistance of the vinylidene fluoride polymer by contacting the vinylidene fluoride polymer with an alkali and calculating the degradation amount of the vinylidene fluoride polymer. The method specifically comprises the following steps: A1. The vinylidene fluoride polymer contacts the alkali to form a mixed solution, wherein the vinylidene fluoride polymer is selected from a vinylidene fluoride polymer solid, a vinylidene fluoride polymer solution or a vinylidene fluoride polymer dispersion, and the alkali is selected from a solid alkali, a liquid alkali or an alkali solution; A2. The fluoride ion concentration of the mixed solution is detected, and the degradation amount is calculated by the following formula: wherein C is the fluoride ion concentration of the mixed solution, V is the volume of the mixed solution, and m is the mass of the vinylidene fluoride polymer in the mixed solution. The present invention quantitatively evaluates the alkali resistance of different vinylidene fluoride polymers by the percentage of degradation reaction of the molecular chain of the vinylidene fluoride polymer after contacting an alkaline substance, and has the advantages of accurate results, rapidity and simplicity, etc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a polymer alkali resistance test, in particular to an alkali resistance test method for a vinylidene fluoride polymer. Background Art

[0002] Vinylidene fluoride polymer is a polymer containing repeating units of vinylidene fluoride (VDF). In addition to the general properties of fluorinated polymers such as high temperature resistance, super weather resistance, corrosion resistance, stain resistance, chemical inertness and extremely low surface energy, it also has special properties such as piezoelectricity, dielectricity and thermoelectricity. It is mainly used in four major fields: petrochemicals, electronics and electrical, fluorocarbon coatings and membrane materials, and has broad development prospects.

[0003] However, the alkali resistance of vinylidene fluoride polymers is generally poor. After contacting alkaline substances, they tend to turn yellow, their mechanical properties deteriorate, and even gel, which affects their subsequent use. Therefore, it is necessary to evaluate the alkali resistance of vinylidene fluoride polymers (including the same vinylidene fluoride polymers obtained by different polymerization processes, different vinylidene fluoride polymers obtained by the same polymerization process, and different vinylidene fluoride polymers obtained by different polymerization processes) so as to select vinylidene fluoride polymer products suitable for downstream applications.

[0004] In the prior art, the evaluation of the alkali resistance of polyvinylidene fluoride polymers usually adopts qualitative analysis or indirect analysis. For example, in the article "Effect of Amide Solvents on Alkali Corrosion Resistance of Polyvinylidene Fluoride" (Plastics, 2015, 44(6): 63-65, 92.), Xu Tong et al. judged the alkali resistance of polyvinylidene fluoride by color difference analysis after contact with alkali. The results showed that the higher the alkali concentration, the lower the brightness of polyvinylidene fluoride. This method belongs to indirect analysis. In the article "Effect of Acid, Base and Oxidant on Aging of Polyvinylidene Fluoride Ultrafiltration Membrane" (Journal of Harbin Institute of Technology, 2017, 49(8): 25-30), Liu Jingyan et al. tested the elongation at break and tensile strength at break of polyvinylidene fluoride membrane before and after immersion in alkali solution to judge the alkali resistance, which also belongs to indirect analysis.

[0005] Patents CN102605620A and CN105797599B characterize alkali resistance by comparing the change in tensile strength at break of polyvinylidene fluoride strips before and after soaking in sodium hydroxide solution for 24-1080 hours. However, tensile strength at break is a macroscopic manifestation of the polymer microstructure. In addition to being related to the alkali resistance of polyvinylidene fluoride, it is also related to factors such as molecular weight, molecular weight distribution, crystallinity, and crystal type. This method is not accurate enough to evaluate alkali resistance.

[0006] Patent CN107083143B characterizes the alkali resistance of a polyvinylidene fluoride sample by measuring the bubbling after immersion in a sodium hydroxide solution for 24 hours. This method is a qualitative observation, and the result is only described as bubbling or no bubbling of the sample, and the test result contains little information.

[0007] At present, there are three main problems in the evaluation method of alkali resistance of vinylidene fluoride polymers: 1. It is impossible to quantitatively evaluate alkali resistance; 2. The method of using the change of physical properties of vinylidene fluoride polymers to characterize alkali resistance requires the manufacture of finished products, which has a long cycle and is not conducive to rapid results, and the physical property test results are affected by other factors; 3. The universality of the test method is poor and can only be used for specific applications. Summary of the invention

[0008] In order to solve the above problems, the present invention provides a method for testing the alkali resistance of vinylidene fluoride polymers with accurate measurement results, rapidity and simplicity.

[0009] The objective of the present invention is achieved through the following technical solutions:

[0010] A method for testing the alkali resistance of a vinylidene fluoride polymer, wherein the alkali resistance testing method quantitatively evaluates the alkali resistance of the vinylidene fluoride polymer by contacting the vinylidene fluoride polymer with an alkali and calculating the degradation amount of the vinylidene fluoride polymer. The principle is that when the vinylidene fluoride polymer meets an alkali, an elimination reaction will occur to produce hydrogen fluoride, and the degradation amount of the vinylidene fluoride polymer after meeting an alkali is calculated by testing the amount of fluoride ions, thereby quantitatively evaluating the alkali resistance of the vinylidene fluoride polymer.

[0011] Specifically, the alkali resistance testing method comprises the following steps:

[0012] A1. A vinylidene fluoride polymer is contacted with a base to form a mixed solution, wherein the vinylidene fluoride polymer is selected from a vinylidene fluoride polymer solid, a vinylidene fluoride polymer solution or a vinylidene fluoride polymer dispersion, and the base is selected from a solid base, a liquid base or an alkaline solution;

[0013] A2. Detect the fluoride ion concentration of the mixed solution and calculate the degradation amount X by the following formula:

[0014]

[0015] Wherein, C is the fluoride ion concentration of the mixed solution, in mg / L; V is the volume of the mixed solution, in L; and m is the mass of the vinylidene fluoride polymer in the mixed solution, in mg.

[0016] In step A2, an ion meter, a spectrophotometer or an ion chromatograph may be used to detect the fluoride ion concentration. Preferably, an ion meter is used to detect the fluoride ion concentration. When the ion meter detects the fluoride ion concentration, the detection object must be an aqueous solution. If the mixed solution formed by the contact between the vinylidene fluoride polymer and the alkali does not contain water, it is necessary to measure a portion of the mixed solution and dilute it in water to obtain the test solution.

[0017] Specifically, when using an ion meter to detect the fluoride ion concentration, it is necessary to first neutralize the mixed solution to obtain a test solution, and then detect the fluoride ion concentration. Preferably, before neutralizing the mixed solution, a centrifuge can be used to centrifuge so that the residual alkali sinks to the lower layer, thereby reducing the mass of the residual alkali in the upper clear liquid.

[0018] When the mixed solution is a dispersion, a neutralizing agent or a buffer solution can be directly added to neutralize the residual alkali to obtain a test solution with a pH of 3-10, and the fluoride ion concentration of the test solution is 0.01-10000 mg / L. Preferably, the mixed solution is first centrifuged in a centrifuge, a portion of the supernatant of the mixed solution is measured, and then a neutralizing agent or a buffer solution is added to neutralize the residual alkali to obtain a test solution with a pH of 3-10, and the fluoride ion concentration of the test solution is ensured to be 0.01-10000 mg / L.

[0019] When the mixed solution is a solution, part of the mixed solution needs to be diluted in water, and then a neutralizing agent or a buffer solution is added to neutralize the residual alkali to obtain a test solution with a pH of 3-10, and the fluoride ion concentration of the test solution is 0.01-10000 mg / L. Preferably, the mixed solution is centrifuged in a centrifuge, part of the supernatant of the mixed solution is diluted in water, and then a neutralizing agent or a buffer solution is added to neutralize the residual alkali to obtain a test solution with a pH of 3-10, and the fluoride ion concentration of the test solution is ensured to be 0.01-10000 mg / L.

[0020] The mass content of water in the test liquid is 70.0-99.9wt%, more preferably 90.0-99.0wt%.

[0021] The pH value of the test solution will affect the alkali resistance test result. Therefore, the pH value of the test solution of the present invention is preferably 5-8.

[0022] Furthermore, the neutralizing agent is selected from at least one of sulfuric acid, hydrochloric acid, phosphoric acid, acetic acid, and oxalic acid; the buffer solution is selected from potassium hydrogen phthalate-hydrochloric acid buffer, disodium hydrogen phosphate-citric acid buffer, citric acid-sodium hydroxide-hydrochloric acid buffer, citric acid-sodium citrate buffer, glacial acetic acid-sodium chloride-sodium citrate buffer (total ionic strength buffer / TISAB).

[0023] The degradation degree of vinylidene fluoride polymer varies greatly with the contact time with alkali. Therefore, it is necessary to ensure that the contact time of the vinylidene fluoride polymer to be quantitatively evaluated (including polyvinylidene fluoride and its products, vinylidene fluoride copolymer and its products) with alkali is the same, and the specific contact time is not limited.

[0024] The vinylidene fluoride polymer of the present invention includes vinylidene fluoride homopolymer, copolymer of vinylidene fluoride and one or more other monomers, blend of vinylidene fluoride homopolymer and other polymers, blend of vinylidene fluoride copolymer and other polymers and their respective related products. Among them, the other monomers are selected from at least one of vinyl fluoride, trifluoroethylene, tetrafluoroethylene, trifluorochloroethylene, perfluoromethyl vinyl ether, perfluoropropyl vinyl ether, acrylic acid and its esters, methacrylic acid and its esters, maleic acid and its esters, citraconic acid and its esters, vinyl acetate, and vinylene carbonate. The other polymers are selected from at least one of poly (methyl) acrylic acid and its esters, polyvinyl acetate, vinylidene fluoride-hexafluoropropylene copolymer, and polytrifluorochloroethylene. The products are selected from at least one of pipelines, valves, rods, capillaries, water treatment membranes, coatings, and lithium battery electrode binders.

[0025] The form of the vinylidene fluoride polymer includes but is not limited to emulsion, particle, strip, and film.

[0026] The base mentioned in the present invention refers to an alkaline substance that can, or can, under certain conditions, cause a vinylidene fluoride polymer to undergo an elimination reaction and produce hydrogen fluoride.

[0027] The alkali is selected from solid alkali, liquid alkali or alkali solution. Preferably, the solid alkali is selected from at least one of lithium hydroxide, sodium hydroxide, potassium hydroxide, lithium carbonate, sodium carbonate, potassium carbonate, lithium bicarbonate, sodium bicarbonate and potassium bicarbonate; the liquid alkali is selected from at least one of methylamine, ethylamine, dimethylamine, trimethylamine, triethylamine, tripropylamine and tributylamine; the alkali solution is selected from at least one of ammonia water, lithium hydroxide solution, sodium hydroxide solution, potassium hydroxide solution, lithium carbonate solution, sodium carbonate solution, potassium carbonate solution, lithium bicarbonate solution, sodium bicarbonate solution, potassium bicarbonate solution, methylamine solution, ethylamine solution, dimethylamine solution and trimethylamine solution.

[0028] Specifically, when the base is a solid base, the solid base is added to the vinylidene fluoride polymer solution or dispersion to form a mixed solution; when the base is a liquid base or an alkaline solution, the vinylidene fluoride polymer is added to the liquid base or the alkaline solution.

[0029] Different alkalis are selected according to different application scenarios of vinylidene fluoride polymers. Preferably, when evaluating the alkali resistance of vinylidene fluoride polymer water treatment membranes in treating wastewater containing a small amount of sodium hydroxide, the alkali can be selected from sodium hydroxide; when evaluating the alkali resistance of vinylidene fluoride polymers for lithium battery electrode binders, the alkali can be selected from lithium hydroxide or lithium carbonate or a mixture of the two.

[0030] According to the above-mentioned test method for the alkali resistance of vinylidene fluoride polymer, the mass ratio of the alkali to the vinylidene fluoride polymer is 0.0001-1000:1, preferably 0.01-100:1, and more preferably 0.1-10:1.

[0031] The contacting form, time and temperature of the base and the vinylidene fluoride polymer can be set according to different application scenarios or test requirements of the vinylidene fluoride polymer to be tested. Specifically, the contacting form includes standing, shaking or stirring.

[0032] The vinylidene fluoride polymer solution or dispersion is formed by adding the vinylidene fluoride polymer to a solvent. The solvent refers to a solvent that can dissolve or disperse the vinylidene fluoride polymer at room temperature or under certain conditions. The solvent is a pure solvent or a mixed solvent, such as a mixed solvent composed of 95% N,N-dimethylformamide and 5% water.

[0033] Preferably, the solvent capable of dissolving or dispersing the vinylidene fluoride polymer is selected from at least one of N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAC), dimethyl sulfoxide (DMSO), N-methylpyrrolidone (NMP), acetone, tetrahydrofuran, water, methanol, ethanol, and ethyl acetate.

[0034] The solvent also includes an auxiliary agent that can help disperse the polyvinylidene fluoride polymer, mainly a surfactant or a solvent that can wet polyvinylidene fluoride. Preferably, the auxiliary agent is selected from at least one of cellulose compounds, ethanol, and acetone.

[0035] The weight ratio of the solvent to the vinylidene fluoride polymer of the present invention is 1-1000:1; preferably, the weight ratio of the solvent to the vinylidene fluoride polymer is 1-500:1, and more preferably 1-100:1. If the amount of solvent used is too high and the mass percentage of the vinylidene fluoride polymer is too low, it is easy to cause the concentration of fluoride ions produced by degradation to be too low. When it is lower than the lower limit of fluoride ion detection, its alkali resistance cannot be tested; when the amount of solvent used is too low, the viscosity of the test liquid is large, which is not conducive to sufficient contact and mixing with the alkali, which will affect the accuracy of the alkali resistance value.

[0036] During the formation of the vinylidene fluoride polymer solution or dispersion or when it is transferred into water, the vinylidene fluoride polymer will form a gel or a coating solution, which can be destroyed by placing, high-speed shearing, violent shaking, stirring, etc. to ensure that the fluoride ions in the measured mixed solution are completely transferred into the water.

[0037] The fluoride ion concentration of the test solution of the present invention is obtained by the following steps:

[0038] B1. Prepare standard solutions: prepare metal fluoride standard solutions of different concentrations;

[0039] B2. Draw a standard curve: measure the potential values ​​of metal fluoride standard solutions with different concentrations and draw a concentration-potential standard curve;

[0040] B3. Measuring the fluoride ion concentration of the test liquid: measuring the potential value of the test liquid, and calculating the fluoride ion concentration of the test liquid according to the standard curve.

[0041] Preferably, the metal fluoride is selected from at least one of sodium fluoride, potassium fluoride or lithium fluoride.

[0042] Preferably, at least 4 metal fluoride standard solutions with different concentrations are prepared.

[0043] The solvent used to prepare the fluoride ion standard solution should be consistent with the solvent used to prepare the test solution. Specifically, when preparing the test solution, 0.5g PVDF, 10g N-methylpyrrolidone (NMP), and 90g water are used to form a mixed solution, and the solvent used to prepare the fluoride ion standard solution should be a 10wt% NMP aqueous solution.

[0044] Compared with the prior art, the present invention has the following beneficial effects:

[0045] 1. The present invention quantitatively evaluates the alkali resistance of different vinylidene fluoride polymers by measuring the percentage of degradation reaction of the molecular chain of the vinylidene fluoride polymer after contact with alkaline substances. The test result is accurate and the influence of factors such as molecular weight and crystallization can be excluded;

[0046] 2. The alkali resistance test method of the present invention is quick, simple, low-cost and easy to use;

[0047] 3. The alkali resistance test method of the present invention has a wide range of applications and is suitable for evaluating the alkali resistance of vinylidene fluoride polymers and related products of different types and in different application occasions. DETAILED DESCRIPTION

[0048] The present invention is further described below in conjunction with specific embodiments, but the present invention is not limited to these specific embodiments. Those skilled in the art should recognize that the present invention covers all possible alternatives, improvements and equivalents within the scope of the claims.

[0049] Example 1

[0050] Draw a fluoride ion standard curve:

[0051] S1. Prepare standard solution: Bake NaF in an oven at 110°C to constant weight, weigh 1.1278 g NaF, add pure water to make up to 500 ml, and prepare a standard solution with a fluoride ion concentration of 1000 mg / L.

[0052] Pipette 1.0mL, 2.5mL, 5.0mL, 10.0mL, 20.0mL and 30.0mL of the above standard solution into a volumetric flask, add 5mL NMP and 10mL TISAB buffer, make up to 50mL with water, and heat to 25°C in a water bath.

[0053] Total ionic strength buffer (TISAB) was prepared by the following steps: 50 ml H2O, 57 ml glacial acetic acid, 58 g sodium chloride, and 12 g sodium citrate were added to a 1000 ml beaker, and stirred to dissolve. The beaker was placed in a cold water bath, and 6 mol / L NaOH solution was added until the pH was between 5.0 and 6.0 (checked with a pH meter), cooled, and diluted to 1000 ml with distilled water.

[0054] S2. Use an ion meter to detect the potential values ​​of the above 6 standard solutions respectively, and draw a fluoride ion concentration-potential standard curve, as shown in the following table:

[0055] 1 2 3 4 5 6 Amount of standard solution pipetted, mL 1.0 2.5 5.0 10.0 20.0 30.0 Fluoride ion concentration, mg / L 20.0 50.0 100.0 200.0 400.0 600.0 Fluoride ion, log C 1.3010 1.6990 2.0000 2.3010 2.6021 2.7782 Potential, mV -181.21 -157.87 -140.38 -122.18 -105.20 -94.80

[0056] The standard curve obtained by fitting is: y = 58.518x-257.29 R 2 =0.9999.

[0057] Alkali resistance test of vinylidene fluoride polymer:

[0058] 1. Prepare the test solution of vinylidene fluoride polymer:

[0059] A1. 35 g of vinylidene fluoride polymer powder A was completely dissolved in 1000 g of N-methylpyrrolidone, 20.00 g of the solution was taken into 6 flasks, 0.5 g of lithium hydroxide and 0.6 g of lithium carbonate were added, and magnetic stirring was carried out at a constant temperature of 20 ° C for 4 hours to obtain 6 mixed solutions.

[0060] A2. Take 6 wide-mouth bottles, add 35g pure water and 10g total ionic strength buffer (TISAB) to each bottle. Centrifuge the above 6 mixed solutions in a centrifuge, take 5.17g of the upper clear liquid and add it to 6 wide-mouth bottles, shake thoroughly, and obtain 6 test solutions with a pH value of 7. Leave them for more than 12 hours.

[0061] 2. Evaluation of alkali resistance

[0062] The potential of 6 test solutions was measured by an ion meter, and the fluoride ion concentration of each test solution was obtained according to the standard curve. The average fluoride ion concentration was calculated and the formula was used. The degradation amount is calculated and used to quantitatively evaluate the alkali resistance of the vinylidene fluoride polymer. The smaller the degradation amount, the better the alkali resistance of the vinylidene fluoride polymer. Conversely, the larger the degradation amount, the worse the alkali resistance of the vinylidene fluoride polymer.

[0063] In the above formula, C is the average value of fluoride ion concentration, 75.65 mg / L, V is the volume of the test liquid, 0.05 L, and m is the mass of the vinylidene fluoride polymer powder A in the test liquid, m=the mass of the measured upper clear liquid×the mass content of the vinylidene fluoride polymer powder A in the mixed liquid=5170×(35 / 1035), as shown in the following table:

[0064]

[0065] Example 2

[0066] Alkali resistance test of vinylidene fluoride polymer:

[0067] 1. Prepare the test solution of vinylidene fluoride polymer:

[0068] A1. Vinylidene fluoride polymer powders A, B, and C (lithium battery binder grade) are three samples produced by three different companies.

[0069] 35g of vinylidene fluoride polymer powder A was completely dissolved in 1000g of N-methylpyrrolidone, and 20.00g of the solution was taken into three flasks. Then 0.5g of lithium hydroxide and 0.6g of lithium carbonate were added respectively, and magnetic stirring was carried out at a constant temperature of 40°C for 4 hours to obtain three mixed solutions, namely, mixed solution A1, mixed solution A2, and mixed solution A3.

[0070] 35g of vinylidene fluoride polymer powder B was completely dissolved in 1000g of N-methylpyrrolidone, and 20.00g of the solution was taken into three flasks. Then 0.5g of lithium hydroxide and 0.6g of lithium carbonate were added respectively, and magnetic stirring was carried out at a constant temperature of 40°C for 4 hours to obtain three mixed solutions, namely mixed solution B1, mixed solution B2, and mixed solution B3.

[0071] 35g of vinylidene fluoride polymer powder C was completely dissolved in 1000g of N-methylpyrrolidone, and 20.00g of the solution was taken into three flasks. Then 0.5g of lithium hydroxide and 0.6g of lithium carbonate were added respectively, and magnetic stirring was carried out at a constant temperature of 40°C for 4 hours to obtain three mixed solutions, namely, mixed solution C1, mixed solution C2, and mixed solution C3.

[0072] A2. Take 9 wide-mouth bottles, add 35g pure water and 10g total ionic strength buffer (TISAB) to each bottle. Centrifuge the above 9 mixed solutions in a centrifuge, take 5.17g of the upper clear liquid and add it to 9 wide-mouth bottles, shake thoroughly, and obtain 9 test solutions, all with a pH value of 7, and leave them for more than 12 hours.

[0073] 2. Evaluation of alkali resistance

[0074] The potential of 9 test solutions was measured by an ion meter, and the fluoride ion concentration of each test solution was calculated according to the standard curve y=58.518x-257.29 of Example 1, and the average fluoride ion concentration was obtained. The degradation amounts of three samples of vinylidene fluoride polymer powder A, B, and C (lithium battery binder grade) were calculated to be 27.82%, 27.11%, and 25.21%, respectively. It can be seen that vinylidene fluoride polymer powder C has the best alkali resistance, while vinylidene fluoride polymer powder A has the worst alkali resistance. The details are shown in the following table:

[0075]

[0076] Example 3

[0077] Draw a fluoride ion standard curve:

[0078] S1. Prepare standard solution: Bake NaF in an oven at 110°C to constant weight, weigh 1.1278 g NaF, add pure water to make up to 500 ml, and prepare a standard solution with a fluoride ion concentration of 1000 mg / L.

[0079] Pipette 1.0mL, 2.5mL, 5.0mL, 10.0mL, 20.0mL and 30.0mL of the above standard solution into a volumetric flask, add 2.5mL DMF and 10mL TISAB buffer, make up to 50mL with water, and heat to 25℃ in a water bath.

[0080] The potential values ​​of the above 6 standard solutions were detected by an ion meter, and a fluoride ion concentration-potential standard curve was drawn, as shown in the following table:

[0081]

[0082]

[0083] The standard curve obtained by fitting is: y = 60.607x-267.47 R 2 =0.9997

[0084] Alkali resistance test of vinylidene fluoride polymer:

[0085] 1. Prepare the test solution of vinylidene fluoride polymer:

[0086] A1. Vinylidene fluoride-hexafluoropropylene copolymer (hexafluoropropylene molar content 2.8-3.0%) powders D, E, and F are three samples produced by three different companies.

[0087] 50g of vinylidene fluoride-hexafluoropropylene copolymer powder D was completely dissolved in 1000g of N,N-dimethylformamide. 20.00g of the solution was taken into three flasks respectively. Then 0.1g of 3% methylamine aqueous solution was added, and magnetic stirring was carried out at a constant temperature of 50℃ for 2 hours to obtain three mixed solutions, namely, mixed solution D1, mixed solution D2, and mixed solution D3.

[0088] 50g of vinylidene fluoride-hexafluoropropylene copolymer powder E was completely dissolved in 1000g of N,N-dimethylformamide. 20.00g of the solution was taken into three flasks respectively. Then 0.1g of 3% methylamine aqueous solution was added, and magnetic stirring was carried out at a constant temperature of 50℃ for 2 hours to obtain three mixed solutions, namely, mixed solution E1, mixed solution E2, and mixed solution E3.

[0089] 50g of vinylidene fluoride-hexafluoropropylene copolymer powder F was completely dissolved in 1000g of N,N-dimethylformamide. 20.00g of the solution was taken into three flasks respectively. Then 0.1g of 3% methylamine aqueous solution was added, and magnetic stirring was carried out at a constant temperature of 50℃ for 2 hours to obtain three mixed solutions, namely, mixed solution F1, mixed solution F2, and mixed solution F3.

[0090] A2. Take 9 wide-mouth bottles, add 35g pure water and 10g total ionic strength buffer (TISAB) to each bottle. Centrifuge the above 9 mixed solutions in a centrifuge, take 5.17g of the upper clear liquid and add it to 9 wide-mouth bottles, shake thoroughly, and obtain 9 test solutions, all with a pH value of 7, and leave them for more than 12 hours.

[0091] 2. Evaluation of alkali resistance

[0092] The potential of 9 test solutions was measured by an ion meter. The fluoride ion concentration of each test solution was calculated according to the standard curve y=60.607x-267.47 of this embodiment, and the average fluoride ion concentration was obtained. The formula The degradation amounts of three samples of vinylidene fluoride-hexafluoropropylene copolymer powders D, E, and F were calculated to be 4.568%, 4.796%, and 5.852%, respectively. It can be seen that vinylidene fluoride-hexafluoropropylene copolymer D has the best alkali resistance, while vinylidene fluoride-hexafluoropropylene copolymer F has the worst alkali resistance. The details are shown in the following table:

[0093]

[0094] Example 4

[0095] Draw a fluoride ion standard curve:

[0096] S1. Prepare standard solution: Bake NaF in an oven at 110°C to constant weight, weigh 1.1278 g NaF, add pure water to make up to 500 ml, and prepare a standard solution with a fluoride ion concentration of 1000 mg / L.

[0097] Pipette 0.25mL, 1.0mL, 2.5mL, 5.0mL, 10.0mL and 20.0mL of the above standard solution into a volumetric flask, add 10mL of TISAB buffer, make up to 50mL with water, and heat to 25℃ in a water bath.

[0098] The potential values ​​of the above 6 standard solutions were detected by an ion meter, and a fluoride ion concentration-potential standard curve was drawn, as shown in the following table:

[0099] 1 2 3 4 5 6 Amount of standard solution pipetted, ml 0.25 1.0 2.5 5.0 10.0 20.0 <![CDATA[Formulation concentration, mg F - / L]]> 5.0 20.0 50.0 100.0 200.0 400.0 Fluoride ion, log C 0.6990 1.3010 1.6990 2.0000 2.3010 2.6021 Potential, mV -231.06 -195.80 -171.67 -154.18 -136.30 -118.65

[0100] The standard curve obtained by fitting is: y = 59.064x-272.34 R 2 =1

[0101] Alkali resistance test of vinylidene fluoride polymer:

[0102] 1. Prepare the test solution of vinylidene fluoride polymer:

[0103] A1. Vinylidene fluoride polymer hollow fiber membranes G, H, and I are three samples produced by three different companies.

[0104] 10 g of each vinylidene fluoride polymer hollow fiber membrane G was added to three containers containing 100 ml of 1 mol / L sodium hydroxide aqueous solution, and 1 g of hydroxypropyl methylcellulose was added to aid dispersion. The mixture was magnetically stirred at a constant temperature of 50°C for 4 hours to obtain three mixed solutions, namely mixed solution G1, mixed solution G2, and mixed solution G3.

[0105] 10 g of each vinylidene fluoride polymer hollow fiber membrane H was added to three containers containing 100 ml of 1 mol / L sodium hydroxide aqueous solution, and 1 g of hydroxypropyl methylcellulose was added to aid dispersion. The mixture was magnetically stirred at a constant temperature of 50°C for 4 hours to obtain three mixed solutions, namely, mixed solution H1, mixed solution H2, and mixed solution H3.

[0106] 10 g of each vinylidene fluoride polymer hollow fiber membrane I was added to three containers containing 100 ml of 1 mol / L sodium hydroxide aqueous solution, and 1 g of hydroxypropyl methylcellulose was added to aid dispersion. The mixture was magnetically stirred at a constant temperature of 50° C. for 4 hours to obtain three mixed solutions, namely, mixed solution I1, mixed solution I2, and mixed solution I3.

[0107] A2. Take 9 100ml volumetric flasks, add 5ml of 1mol / L hydrochloric acid solution and 20g of total ionic strength buffer (TISAB) to each volumetric flask. Take 5ml of the above 9 mixed solutions and add them to 9 volumetric flasks, and make up to 100ml respectively to obtain 9 test solutions with a pH value of 7, and leave them for more than 12 hours.

[0108] 2. Evaluation of alkali resistance

[0109] The potential of 6 test solutions was measured by an ion meter. The fluoride ion concentration of each test solution was calculated according to the standard curve y=59.064x-272.34 of this embodiment, and the average fluoride ion concentration was obtained. The formula The degradation amounts of the three samples of the vinylidene fluoride polymer hollow fiber membrane G, H, and I were calculated to be 1.566%, 1.420%, and 0.7968%, respectively. It can be seen that the vinylidene fluoride polymer hollow fiber membrane I has the best alkali resistance, and the vinylidene fluoride polymer hollow fiber membrane G has the worst alkali resistance. The specific results are shown in the following table:

[0110]

[0111] Comparative Example 1

[0112] Vinylidene fluoride polymer powders A, B, and C were mixed with conductive agents, positive electrode materials LiNi 0.8 Co 0.1 Mn 0.1 After mixing O2 (NCM811) in a ratio of 1.5:3:95.5, N-methylpyrrolidone was added to prepare a slurry, the solid content was controlled to 70%, and stirred for 4 hours under anhydrous and oxygen-free conditions. The slurry temperature was controlled below 50°C by cooling water. It was found that the slurries using vinylidene fluoride polymers A and B had gel, while the slurry using vinylidene fluoride polymer C still had fluidity.

[0113] Comparative Example 2

[0114] 10g of each of the vinylidene fluoride polymer hollow fiber membranes G, H, and I were added to 100ml of 1mol / L sodium hydroxide aqueous solution and soaked at 50℃ for 168 hours. The samples were taken out, washed with pure water until neutral, dried, and tested for elongation at break. The results are shown in the following table:

[0115] G H I Before soaking, % 154.0 146.8 146.6 After soaking, % 65.4 64.7 64.4 Decrease ratio, % 57.5 55.9 56.1

[0116] As can be seen from Examples 1-4 and Comparative Examples 1-2, Comparative Example 1 can only conclude that the alkali resistance of vinylidene fluoride polymer C is better than that of vinylidene fluoride polymers A and B, but it is impossible to know whether the alkali resistance of samples A and B is good or bad; Comparative Example 2 compares the changes in elongation at break before and after alkali solution immersion, but the factors affecting the change in elongation at break include molecular weight and crystallization in addition to alkali resistance, which is a comprehensive manifestation of multiple factors. The present invention quantitatively evaluates the alkali resistance of different vinylidene fluoride polymers by the percentage of degradation reactions of the molecular chains of vinylidene fluoride polymers after contact with alkaline substances. The test results are accurate and the influence of factors such as molecular weight and crystallization can be excluded; and the test method of the present invention is fast, simple, low-cost, and easy to use, and is suitable for the evaluation of alkali resistance of vinylidene fluoride polymers and related products of different types and different application occasions.

Claims

1. A method for testing the alkali resistance of vinylidene fluoride polymers used as lithium battery electrode binders, characterized in that: The alkali resistance testing method comprises the following steps: A1. The vinylidene fluoride polymer is contacted with a base to form a mixed solution, wherein the vinylidene fluoride polymer is a vinylidene fluoride polymer solution, and the base is selected from lithium hydroxide or lithium carbonate or a mixture of the two; the mass ratio of the base to the vinylidene fluoride polymer is 0.0001-1000:1; A2. Take a portion of the mixed solution and dilute it in water, and add a neutralizing agent or a buffer solution to neutralize the residual alkali to obtain a test solution with a pH of 5-8, and the fluoride ion concentration of the test solution is 0.01-10000 mg / L; detect the fluoride ion concentration of the test solution, and calculate the degradation amount X of the vinylidene fluoride polymer by the following formula: Wherein, C is the fluoride ion concentration of the mixed solution, in mg / L; V is the volume of the mixed solution, in L; m is the mass of the vinylidene fluoride polymer in the mixed solution, in mg; the alkali resistance of the vinylidene fluoride polymer is quantitatively evaluated by the degradation amount.

2. The method for testing the alkali resistance of vinylidene fluoride polymer according to claim 1, characterized in that: The vinylidene fluoride polymer solution is formed by adding the vinylidene fluoride polymer into a solvent, and the mass ratio of the solvent to the vinylidene fluoride polymer is 1-1000:

1.

3. The method for testing the alkali resistance of vinylidene fluoride polymer according to claim 2, characterized in that: The solvent is selected from at least one of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, N-methylpyrrolidone, acetone, water, methanol, ethanol, tetrahydrofuran and ethyl acetate.

4. The method for testing the alkali resistance of vinylidene fluoride polymer according to claim 1, characterized in that: The fluoride ion concentration of the test liquid is obtained by the following steps: B1. Prepare standard solutions: prepare metal fluoride standard solutions of different concentrations; B2. Draw a standard curve: measure the potential values ​​of metal fluoride standard solutions with different concentrations and draw a concentration-potential standard curve; B3. Measuring the fluoride ion concentration of the test liquid: measuring the potential value of the test liquid, and calculating the fluoride ion concentration of the test liquid according to the standard curve.

Citation Information

Patent Citations

  • Method for preparing film material by coating polyvinylidene fluoride on glass fiber cloth

    CN102605620A

  • A kind of graphene modified hollow fiber membrane and preparation method thereof

    CN105797599B

  • Baking-type waterborne silicone fluoropolymer coatings, coatings, and their formation methods

    CN107083143B